Enhancing learning and teaching : student feedback in medical and health sciences - Nair, Chenicheri Sid; Mertova, Patricie, 1975- (Chandos learning and teaching series., 2015)
Student feedback has appeared in the forefront of higher education quality, in particular the issues of effectiveness and the use of student feedback to improve higher education teaching and learning, and other areas of student tertiary experience. Despite this, little academic literature has focussed on the experiences of academics, higher education leaders and managers. The final title in the Chandos Learning and Teaching Series to focus on student feedback, Enhancing Learning and Teaching through Student Feedback in the Medical and Health Sciences expands on topics covered in the previous p.